Problem-Based Learning Tool Integrated with Education for Sustainable Development on Biodiversity Topic to Improve Science Literacy - Shabrina*, Anisa; Suhartini, Suhartini; Huang, Tzou Chi (Universitas Syiah Kuala, 2024)
Education for sustainable development (ESD) has become a focus in learning in line with demand in biology learning outcomes in the merdeka curriculum. Problem based learning (PBL) with the integration of ESD prepare students with science abilities considering the fact that students' scientific literacy in Indonesia is still very low. This research aims to develop ESD-integrated PBL learning tool as a reference that teachers can use in implementing learning with ESD approach and to determine the effectiveness of learning tool in improving students' scientific literacy. This research used ADDIE model; analysis, design, development, implementation and evaluation. The developed learning tool consists of lesson plan, worksheet and learning assessment instruments. This research instrument consists of validation questionnaire by expert validators and teachers, students response questionnaire, and scientific literacy questions. The results of this research showed that the developed learning tool was feasible and could be used in classroom based on the assessments of expert validators and teachers. The worksheet developed received a good response from students. Based on the n gain analysis, the application of PBL integrated ESD learning tool increases students' scientific literacy skills in the medium category